Characteristics of basil in aspects of digital information retrieval and data mining - Varin Chouvatut (2019)
© 2019 Taiwan Academic Network Management Committee. All rights reserved. This research aims to propose a novel process for classifying two types of basil, which have different species but share common genus, based on main characteristics of their leaves. One type of the basil proposed in this research is called holy basil and another type is called sweet basil. Considering their leaves, both types have similar features in various points of view, for example, their color shade, size or dimensions, scribbled patterns of the leaf edge, etc. They have a lot of similar features because they share the same genus. However, their similar features are the challenged characteristics this research aims to explore and also to demonstrate how well our proposed method work.